THE SEMANTIC ROLE OF AGENTIVE PASSIVES FOUND IN ENGLISH NOVELS - Luh Putu Ratna Sari; I Nyoman Sedeng; I Nyoman Udayana (Universitas Pendidikan Ganesha, 2021)
This study entitled The Semantic Role of Agentive Passives Found in English Novels that focuses on what the semantic role of agentive passive in English novels played. The data were taken from five English novels entitled; the adventures of Pinocchio, charlotte’s web, a wrinkle in time, Peter and wendy, and The land of the stories; beyond the kingdoms. This study used the documentation method to collect the data and applied the qualitative method to analyze the data. The theory that was applied in this study was the theory of semantic role proposed by Kroeger (2005) and the theory of agentive passive by Quirk (1972). Based on the analysis, all the semantic role were found in agentive passive; patient, theme, recipient, beneficiary, agent, instrument, location, source, experiencer, stimulus, goal, path, and accompaniment. However in the agentive passive without expressed agent, the semantic roles of agent were never found